Knowledge management strategy in property management : a review - Razali, Muhammad Najib (2008)
This paper describes the theoretical approach the concept of knowledge management to be implemented in property management companies in Malaysia. The KM strategy which is a conceptual model for this paper, formulated from various literature surveys. This will then be a conceptual model for this study. This study is based on conceptual design framework on knowledge management approach for property management companies. Case study will be among registered property management companies registered with Board of Valuers, Estate Agents and Appraisers (BOVEA). Knowledge Management is relatively a new terminology for in real estate industry. Theoretically, it will enhance the performance the organisation in many ways. This study will give significant contribution to the property management industry in Malaysia. As business environment is evolve which knowledge is vital, property management players should participate in globalisation changes. This concept will in turn revolutionise organisation into more innovative and competitive companies.